Answer:
Step-by-step explanation:
Your answer
5.55 per square foot
Mark it as Brainlist. Follow me for more answer.
Answer:
Therefore the required result is 9x-2y =0.
Step-by-step explanation:
Given equation are
x-3y =6.....(1)
-8x-y=6 .....(2)
Subtracting equation (2) from (1)
x - 3y = 6
-8x - y= 6
+ + - [ The sign of equation (2) will be change in case of
_________ subtraction and in case of plus the signs remains same ]
(x+8x)-3y+y=6-6 [ adding the like terms]
⇒9x-2y =0
Therefore the required result is 9x-2y =0.
B
the probability of an event ( A<span> ), given that another ( </span>B<span> ) has already occurred.
</span>
Answer:
It's y=4x+3
Step-by-step explanation:
if you find the slope m=(y2-y1)/(x2-x1). Then you know the y-intercept is 3 because it gives you the point (0,3).
Answer:
90 miles
Step-by-step explanation:
The person who answered first explained it well, so I dont have to.
have a nice day :)